Pengaruh Sikap pada Ebook dan Sikap pada Buku Fisik terhadap Minat Baca Masyarakat di Era Industri 4.0 - Dewi Nurbaiti; Mariah Mariah (Jurnal Logistik Indonesia, 2020)
One of the creative industry’ products which are inside of it are writings and pictures produced from one's creative thinking is book. For some communities, reading physical books are still an option if compared with reading digital book or called e-book. This is related with the age, neighborhood, social status and the level of education. Along with the development of the times, there has been a lot of growing up the publishing industry and also the profession of book writer, but it is not end by printing physical books, but in digital platform only. The process of e-book selling is increase every day and it become a capable industry to sustain the economic needs of communities. The quantitative research that compiled by collecting questionnaire data to the people of Jakarta and surrounding areas provides data presentation that Ebooks and physical books are important factors that influence people's interest in reading in the industrial era 4.0. Both types of books have their own appeal to attract individual mints according to different age groups.